Systematic classification of uterine cervical elongation in patients with pelvic organ prolapse. (May 2016) - Mothes, Anke R.; Mothes, Henning; Fröber, Rosemarie; Radosa, Marc P.; Runnebaum, Ingo B.
Abstract: Objective: To define and classify cervical elongation, to compare uterine measurements after prolapse hysterectomy with a non-prolapse control group, and to associate stage of prolapse and degree of cervical elongation. Study design: This was a single-centre retrospective case-control study conducted at the University Hospital, Urogynaecological Unit, with a certified urogynaecological surgeon. Data were collected from patients with and without pelvic organ prolapse (POP) who underwent laparoscopically assisted vaginal hysterectomy. Post-hysterectomy uterine cervical elongation was examined using the corpus/cervix ratio (CCR), calculated from measurements taken on photographs. Cervical elongation was classified as physiological (grade 0, CCR > 1.5) grade I (CCR > 1 and ≤1.5) grade II (CCR > 0.5 and ≤1), and grade III (CCR ≤ 0.5). Results: Cervical elongation was detected in 288/295 (97.6%) patients in the prolapse group (grade I, 44/288 [15.2%]; grade II, 212 [73.6%]; grade III, 32 [11.1%]). Mean CCR was greater among those with stage II/III than among those with stage IV prolapse (1.0 ± 0.4 vs . 0.8 ± 0.2; p  < 0.001). Grades of cervical elongation and prolapse stages were associated ( p  < 0.001). Grade I cervical elongation was detected in 26/69 (37.6%), grade II in 5/69, and grade III in 0/69 patients of the control group. Cervical elongation was found more often in the prolapse group compared to the control group ( p  < 0.001). Mean total uterine length did not differ between the prolapse and control groups (8.0 ± 1.6 vs . 8.2 ± 1.3 cm), but mean calculated cervical length was greater in the prolapse group than in the control group (4.4 ± 1.1 vs. 3.1 + 0.8 cm; p  < 0.001). Conclusions: Uterine cervical elongation is found in patients undergoing hysterectomy for pelvic organ prolapse. Cervical elongation grades and prolapse stages are correlated. Defining uterine cervical elongation based on corpus/cervix ratio with grades I–III could be a valuable basic tool for further research.